Remição de pena pelo estudo e direitos humanos: aplicação do direito à luz do realismo jurídico - Mendonça, Thereza Michelle Lima Lopes de (2013)
The jurisdictional activity in recent years has adopted a method of acting that is guided interpretive freedom in the magistrates that are based on personal experiences to utter a sentence. This attitude was observed in the broad interpretation of redemption penalty of the study that was inserted in the law by setting broad interpretation of LEP/84 which provided only redemption through work. Since then, a conception of a right practical and real, existing, moved away from the hypothetical conception of law, influenced by Human Rights. Thus, jurists viewed education as a means resocializing the individual. This attitude has made us observe features of the American Legal Realism, theorized by Benjamin Cardozo, in understanding what is right even if it is at the time of its application by judges, before each case. The analysis of § 2 of art. 5 of the Constitution shows the basis for this interpretation, guided by the possibility of implementation of Human Rights is not inserted in the Brazilian legislation. Given this fact, we can see the process of integration and implementation of the rights and guarantees not written in the Constitution, but present in human rights treaties to which Brazil is a signatory. The slowness of the Legislature before the draft Law which spanned redemption penalty of the study, did not halt the legal thinking and your attitude on this issue see Human Rights in a more humane to secure the rights of the imprisoned and solidify their human dignity. Thus, boards and tribunals emerged a new way of redeeming worth: redemption through the study. This sequence of decisions made sprout a new law, constituted within the forums and courts, causing the STJ to edit a Precedent 341, showing that the understanding that "the frequency of formal education course is because of the redemption of part time execution of sentence under a closed or semi-open." Understanding this that justified a series of trial, the result of extensive interpretation of LEP/84 and the direct influence of Human Rights, which can be analyzed from the characteristics of the Legal Realism.